A proposed resolution to the paradox of drug reward: Dopamine's evolution from an aversive signal to a facilitator of drug reward via negative reinforcement. (September 2015) - Ting-A-Kee, Ryan; Heinmiller, Andrew; van der Kooy, Derek
Highlights: The paradox of drug reward is that plant neurotoxins deter predation yet also act as reinforcers. We suggest that dopamine – traditionally associated with reward – initially signaled aversion. The ability to regulate this aversion lead to reward via negative reinforcement. Abstract: The mystery surrounding how plant neurotoxins came to possess reinforcing properties is termed the paradox of drug reward. Here we propose a resolution to this paradox whereby dopamine – which has traditionally been viewed as a signal of reward – initially signaled aversion and encouraged escape. We suggest that after being consumed, plant neurotoxins such as nicotine activated an aversive dopaminergic pathway, thereby deterring predatory herbivores. Later evolutionary events – including the development of a GABAergic system capable of modulating dopaminergic activity – led to the ability to down-regulate and 'control' this dopamine-based aversion. We speculate that this negative reinforcement system evolved so that animals could suppress aversive states such as hunger in order to attend to other internal drives (such as mating and shelter) that would result in improved organismal fitness.